Repair of large palatal fistula using tongue flap - Fejjal Nawfal; Brahmi Hicham; Bekkali Achraf; Belkacem Rachid (Wolters Kluwer Medknow Publications, 2014)
Large palatal fistulas are a challenging problem in cleft surgery. Many techniques are used to close the defect. The tongue flap is an easy and reproductible procedure for managing this complication. The authors report a case of a large palatal fistula closure with anteriorly based tongue flap.